Future Asian space : projecting the urban space of new East Asia - Viray, Erwin; Davisi Boontharm; Hee, Limin (NUS Press for Centre for Advanced Studies in Architecture (CASA), Dept. of Architecture, National University of Singapore, 2012)
Rapid technological, economic, social and cultural changes are transforming the idea of "Asian space." With the shift to a global economy and an urban population explosion, Asian cities have become a mainstay of progress, national pride, identity, and positioning on the global stage. The extraordinary pace and intensity of the changes have created a situation unique in the history of urban development. Despite the immense diversity of Asian countries, "Asia-ness" is often treated as a distinctive quality that has emerged from unique recent circumstances affecting Asian urbanizations as a whole. In Future Asian Space, 15 authors explore broad concepts relating to the creation and re-creation of "Asian space" and contemporary Asian identity, and their examination of different sites and research approaches highlights the difficulty of pinpointing what Asia-ness is, or might become. Appropriate design and planning of cities is a critical element in building a sustainable future and coping with environmental, social and cultural problems. Future Asian Space is designed to stimulate interests and engagement in discussions of the Asian city, and its trajectories in architecture and urbanism., but the authors' conclusions will intrigue anyone interested in teh future of cities and urban life in Asia.